EVALUASI PENGGUNAAN OBAT ANTITUBERKULOSIS (OAT) PADA PASIEN TB PARU DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2020 - Sinulingga, Amanda Safithri; Boru Situmorang, Novidawati; Gabena Siregar, Mas (Jurnal FARMASIMED (JFM), 2021)
Tuberculosis is a disease caused by the bacterium Mycobacterium tuberculosis, a first- line anti-tuberculosis drug, namely Isoniazid (H) and Rifampicin (R). The increase in the number of Tb Lung patients from 2019 to 2020 at the RS Grandmed Lubuk Pakam encouraged researchers to conduct this study. The purpose of this study was to determine the description of the use of antituberculosis drugs and the rationality of the use of anti-tuberculosis drugs in pulmonary TB patients in RS Grandmed Lubuk Pakam in 2019. This study was a descriptive (non-experimental) study with retrospective data collection taken from patient medical records. Pulmonary tuberculosis at RS Grandmed Lubuk Pakam. Data was collected using purposive sampling technique in accordance with the inclusion criteria and exclusion criteria using the Data Collection Sheet. The number of samples used in the study is 76 medical records of patients diagnosed with pulmonary TB. Data analysis was performed using the Univariate with the help of SPSS. Results of the distribution of treatment duration data that most patients underwent treatment for <6 months, as many as 31 people (19.9%). Followed by patients with exactly 6 months length of 30 people (0.39%). Whereas patients from 6 months 16 people (21.1%). And the number of Chronic Disease that suffered by Diabetes Mellitus patients was 24 patients (14.5%). All three have a significant relationship to the patient's treatment outcomes. Whereas at the age range 18-24 years, 44 people (57.9%) were affected by pulmonary TB. and The results of the evaluation of the rationality of pulmonary TB treatment are the exact indications of (97.4%), (74 patients), the right patients by 100% (76 patients), the right drugs by (97.4%) (74 patients), and the correct dosage of 100% ( 76).